PENGEMBANGAN MEDIA POP UP BOOK TERHADAP HASIL BELAJAR SISWA KELAS II SEKOLAH DASAR - Latifah, Nadlirotul; Galuh Kartika Dewi; Satrio Wibowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by developing pop up book learning media to improve the learning outcomes of class II students at SDN Sidokepung 1 Sidoarjo in Pancasila education learning. The aim of this research is to find out whether the Pop Up Book media is suitable for use with second grade elementary school students and to find out the learning outcomes of second grade elementary school students after using pop up book media. This research uses the Research and development (R&D) development method which uses 7 procedures, namely potential and problems, data collection, product design, product validation, product revision, product testing, design revision. This research was conducted at SDN Sidokepung 1 Sidoarjo which consisted of 19 samples. The results of media validation produced 81% data categorized as